Assessing organic fouling of ultrafiltration membranes using partition coefficients of dissolved organic matter in aqueous two-phase systems. (November 2022) - Xu, Fanchao; Li, Huixin; Liu, Huiting; Cui, He; Qu, Yao; Yin, Daqiang; Qu, Xiaolei
Abstract: Organic fouling caused by dissolved organic matter (DOM) is a critical challenge for membrane technologies. In this study, prediction models for the fouling of commercial polyether sulfone (PES) and regenerated cellulose (RC) ultrafiltration membranes by DOM were established based on the hydrophobicity of DOM. The organic fouling behavior of 40 natural water samples collected from Lake Taihu was investigated. The fouling propensity of water samples on ultrafiltration membranes was evaluated using the fouling index (FI). The hydrophobicity of DOM in water samples was quantified by its partition coefficient in an aqueous two-phase system ( K ATPS ). The FI of water samples on RC membranes was lower than that on PES membranes due to stronger repulsive Lewis acid-base interactions, which reduced DOM-membrane interactions. A significant positive correlation was found between K ATPS and FI, suggesting the important role of DOM hydrophobicity in the organic fouling of ultrafiltration membranes. FI prediction models using K ATPS as the variable were established using a training group containing 20 water samples for PES and RC membranes, respectively. The resulting models were then validated using the additional 20 water samples, which suggested good prediction power (RMSE = 1.65). The pH effect on the organic fouling can be adequately predicted by the same model with K ATPS values measured at given pH. The results suggest that K ATPS can be used as a convenient index for assessing the initial organic fouling of ultrafiltration membranes by freshwater DOM. Graphical abstract: Image 1 Highlights: Partition coefficient of DOM in ATPS ( K ATPS ) was used to scale its hydrophobicity. K ATPS significantly correlates with the fouling index of DOM on UF membranes. DOM hydrophobicity plays an important role in the organic fouling of UF membranes. Prediction models were established and validated for organic fouling of UF membranes. The pH effect on the organic fouling can be explained using these prediction models.